(x+1)+(x-2)=3

Simple and best practice solution for (x+1)+(x-2)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1)+(x-2)=3 equation:


Simplifying
(x + 1) + (x + -2) = 3

Reorder the terms:
(1 + x) + (x + -2) = 3

Remove parenthesis around (1 + x)
1 + x + (x + -2) = 3

Reorder the terms:
1 + x + (-2 + x) = 3

Remove parenthesis around (-2 + x)
1 + x + -2 + x = 3

Reorder the terms:
1 + -2 + x + x = 3

Combine like terms: 1 + -2 = -1
-1 + x + x = 3

Combine like terms: x + x = 2x
-1 + 2x = 3

Solving
-1 + 2x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 2x = 3 + 1

Combine like terms: -1 + 1 = 0
0 + 2x = 3 + 1
2x = 3 + 1

Combine like terms: 3 + 1 = 4
2x = 4

Divide each side by '2'.
x = 2

Simplifying
x = 2

See similar equations:

| 112.5= | | 20a^2-a-1=0 | | 5s-8=6 | | ln[2x]=0.66 | | 1.5/6=10?p | | Ln(2*x+3)=1.76 | | 2x-30=58 | | 3+n(4)=15 | | 7x-6+6x+2=180 | | 3x+11=33 | | 16x-2+11x-7=180 | | 16x-6+14x+6=180 | | 5x+1+5x-2=30 | | 20x+40x=180 | | 4x^4-12x^3+37x^2-42x+k=0 | | y+4=.5(x+4) | | 5x(x+3)+4=9-(x+1) | | y+9=-7(x+9) | | 5/6(9-6)y= | | U=6i-4j-23k | | 4x*4x+2x*2x=30 | | y=x^4-32x^2-144 | | y+5=-0.6(x+2) | | d/dx(x^11) | | (x*x)-11x=-28 | | 14x+12+15x+5=180 | | y-5=-1.667(x+3) | | (x-2)*(x-2)=9 | | 29x+3+31x-3=180 | | 28x+1+27x+4=180 | | 7x=5(2x-1) | | x+90+110+x=180 |

Equations solver categories